The Histopathological Evaluation of Effects of Application of the Bovine Amniotic Fluid with Graft on Peri-Implant Bone Regeneration - Istek, Ozmen; Tanrisever, Murat; Eroksuz, Hatice; Karabulut, Burak; Ozcan, Erhan Cahit; Bingul, Muhammet Bahattin; Dundar, Serkan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2023)
This study aimed to determine the effects of bovine amniotic fluid combined with bone graft in treating peri-implant bone defects with guided bone regeneration. Twenty female Sprague-Dawley rats were divided into two groups. Bone sockets with a diameter of 4 mm in the coronal part and a diameter of 2.5 mm in the apical part of the implant were created into the corticocancellous bone in the metaphyseal parts of the right tibia bones of all subjects. Implants with a length of 4 mm and a diameter of 2.5 mm were placed in the bone sockets. In the sham surgery group (n = 10) was the circumferential bone defect equivalent to half of the 4-mm implant length, which occurred between the implant and the bone, filled with bovine xenograft. Bovine xenografts were filled with amniotic fluid mixture in the experimental group (n = 10). After 8 weeks of recovery, all rats were sacrificed. The implants were extracted from the soft tissues and the surrounding bone. Subsequently, the bones were decalcified and prepared for histological analysis. The percentage of newly regenerated bone (NRB) formation and fibrosis in the bone defect area around the implant was calculated from all sections. NRB was found in 37.4 +/- 4.4% of controls and 41.4 +/- 2.63% of test animals (P<0.05 and P=0.024, respectively). Fibrosis formation was found at a rate of 38.6 +/- 5.06% in the control group and 33.2 +/- 5.38% in the test group (P<0.05 and P=0.033, respectively). It was considered that combining bovine amniotic fluid with bone transplant could be a useful way of treating bone abnormalities.
Keywords: Bone graft; Bovine amniotic fluid; Guided bone regeneration; Peri-implant bone defect; Tibial bone